Pengembangan Keprofesian Berkelanjutan bagi Guru Sekolah Dasar - Cahyaningtyas Tri Wijiutami; Wahjoedi Wahjoedi; Ery Try Djatmika R. W. W (Graduate School of Universitas Negeri Malang, 2020)
Abstract: The purpose of this research are: (1) study the implementation of the PKB program for elementary school teachers (2) the effectiveness of the PKB program for elementary school teachers. The approach of this research is a qualitative research approach and the type of the research is case study. Data obtained from interviews, observations, and documentation. Based on the acquisition of data generated in the study, it is concluded: (1) The implementation of the PKB program in the form of self-development, scientific publications, and innovative works has been running, (2) The effectiveness of the implementation of the PKB program has not been carried out effectively and optimally, especially in scientific publication activities.Abstrak: Pelaksanaan penelitian ini dengan tujuan untuk (1) mengkaji tentang pelaksanaan program PKB guru sekolah dasar dan (2) efektivitas program PKB guru sekolah dasar. Penggunaan pendekatan pada penelitian ini yaitu pendekatan penelitian kualitatif dengan jenis penelitian case study (studi kasus). Perolehan data didapat dari wawancara, observasi, dan dokumentasi. Berdasarkan perolehan data yang dihasilkan dalam penelitian, maka disimpulkan (1) pelaksanaan program PKB berupa pengembangan diri, publikasi ilmiah, dan karya inovatif sudah berjalan, (2) efektivitas pelaksanaan program PKB belum terlaksana secara efektif dan optimal khususnya pada kegiatan publikasi ilmiah.